An Authentication of Carpooling Apps Using OTP and Fingerprint - Shamsudin, Muzammil Fahmi; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2021)
Many user passwords being leaked through security breaches of user account nowadays. Two-factor authentication (2FA) method of authenticating using a One-Time Password (OTP) and fingerprint was proposed for a carpooling application (app) to enhance the security of the password authentication in such circumstances. 2FA implementation aims at strengthening security by deploying secondary authentication tokens while the OTP was developed by utilizing the SMS system by sending users a message containing a string of code. Implementing OTP and fingerprint authentication to the Book A Seat Carpool application is a method of mitigating the security loopholes of having a password-only authentication method. Agile Model is used as the methodology for flexibility to the developer in order to complete the Android Studio with Java programming language, and Firebase Database is chosen as the development tool. With this application, user can register their account and verified using phone number, authenticate with fingerprint to log in, add ride details, update details, and logout from the application. This application is expected to reduce the risks of attacks on the breach of user account details.